2023
DOI: 10.5539/jel.v12n2p145
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Learning Experience Provision Models That Synergize the Knowledge of Suan Dusit University to Enhance Proper Development of Young Children

Abstract: This research article aims to 1) determine the knowledge and experience of early childhood education of Suan Dusit University, and 2) develop and study the effectiveness of learning experience provision models that synergize the knowledge of Suan Dusit University to enhance the proper development of young children according to the 75/75 criteria. Data is obtained from personnel of 87 various agencies of Suan Dusit University, e.g., deans, directors, managers, chairpersons of programs, heads of departments, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Due to the pandemic, people have been forced to adjust themselves to the 'New Normal' whereby working and learning have been digitalized, and the emphasis has been placed on further developing educational technology. Nevertheless, most studies indicated that online learning demotivates and reduces students' participation (Alshwiah, 2022;El-Sayad et al, 2021;Keesookpun et al, 2023;Jitsupa et al, 2022).…”
mentioning
confidence: 99%
“…Due to the pandemic, people have been forced to adjust themselves to the 'New Normal' whereby working and learning have been digitalized, and the emphasis has been placed on further developing educational technology. Nevertheless, most studies indicated that online learning demotivates and reduces students' participation (Alshwiah, 2022;El-Sayad et al, 2021;Keesookpun et al, 2023;Jitsupa et al, 2022).…”
mentioning
confidence: 99%